Manner of death [large type] - Cook, Robin, 1940- (Thorndike Press large print high octane., 2023)
"Due to Jack Stapleton's ongoing recovery from his near-death bicycle accident, his wife Laurie Montgomery, the NYC chief medical examiner, is carrying the load both at work and at home. She insists a pathology resident named Ryan Sullivan assist her on a suicide autopsy, and when Ryan himself appears on the medical examiner's table days later, an apparent death by suicide, Laurie's guilt compels her to try to understand why. Jack's autopsy on the resident opens the possibility that the death wasn't suicide but instead a staged homicide. Thus begins a dangerous inquiry into a highly lucrative cancer diagnostics company, which might just cost Laurie her life"--